Effects of mechanical factors on the peeling of cassava - Sagragao, Jesus G.; Tan, Daniel Leslie S. (Annals of Tropical Research, 2008)
This study was conducted to determine the effects of the clearance distance angular speed and direction of rotation of the rollers to the mechanical peeling of cassava. A device consisting of two furrowed rollers with straight corrugations about 2 mm deep, lever root presser and driving mechanism all attached to the frame was evaluated according to its peeling recovery and degree of peeling at the following factor combinations: clearance distance between rollers at 80% and 90% of the diameter of the roots, three angular speed combinations at 175 x 144 rpm, 175 x 180 rpm and 175 x 405 rpm and directions of rotations (the same and opposite) of the rollers. The Lakan variety of cassava was used in the evaluation. The cassava root with at least uniform diameters of 35 mm, 50 mm and 65 mm was fed individually, parallel to the axial rotation of the rollers then pressed to the rollers. Results indicated that the efficient peeling of the cassava roots was attained at 175 x 405 rpm at the 90% clearance distance of the same direction of rotation of the rollers.